Code for simulating metapopulation dynamics of L. pulmonaria in Moor et al. (2022): Rebuilding green infrastructure in boreal production forest given future global wood demand. J. Appl. Ecol. (In press) - Fabritius, Henna (Zenodo, 2022)
This file repository contains analysis codes used to simulate Lobaria pulmonaria metapopulation dynamics on the simulation output of Heureka forest simulation software. The analysis codes have been used to analyze L. pulmonaria dynamics under various forest management scenarios in Northern Sweden in Moor et al. (2022): Rebuilding green infrastructure in boreal production forest given future global wood demand. J. Appl. Ecol. (In press). For further details on the L. pulmonaria analyses, see Appendices S6-S7 of Moor et al. (2022). The file repository contains the following codes: * LPUL Metapopulation (col-ext) hierarchical simulation over Heureka-output tree lists.r This is the code for simulating L. pulmonaria metapopulation dynamics. It reads in a treelist made from Heureka output, simulation landscape file (incl.a distance matrix of the host tree stands) and OpenBUGS CODA files that contain the posteriors of the fitted L. pulmonaria occupancy and colonization-extinction models. See Moor et al. (2022) appendices S6-S7 for details. * Generation of individual trees from Heureka output.r This code reads the treelist of a Heureka simulation output file that contains the development of age cohorts of tree groups. From this information, we estimate the proportion of L. pulmonaria host trees (P. tremula and S. caprea) and randomize individual trees to the landscape. See Moor et al. (2022) appendices S6-S7 for details. * S1_randomize_coordinates.r A function source file for the individual tree generation file. * Create a stand distance matrix & attribute file.r This file creates a distance matrix of the host tree stands in the study area landscape, which is needed for the metapopulation simulations.